Interactive effects of soil moisture, organic amendment and herbicide application on fipronil degradation and structure functional potential of soil microbial community in tropical paddy soil - Preethu, D C; Ashoka, K R; Bhagyalakhsmi, T; Kirankumar, N; Vijaykumar, L; Yogananada, S B (Plant Science Today, 2026)
Fipronil degradation followed first-order kinetics. In sterile soil, residues declined slowly from 2.43–1.05 µg g-1 over 30 days, with 30 % dissipation and a half-life of 54.15 days. In non-sterile soil, degradation was faster, decreasing from 1.11–0.02 µg g-1, corresponding to 79.28 % dissipation and a half-life of 11.53 days. Microbial activity accelerated degradation nearly fivefold, contributing 49 % to total dissipation. Fipronil application initially suppressed bacterial and fungal populations, which recovered within 10–30 days, while actinomycetes were largely unaffected. Organic matter (OM) under flooded conditions enhanced bacterial populations (6.61 × 10⁶ CFU g-1 soil), whereas fungal populations were higher under OM at field-capacity moisture (4.04 × 10⁴ CFU g-1 soil) at 30 days after application (DAA). Enzymatic activities showed transient inhibition followed by recovery, with higher dehydrogenase activity in flooded + OM soils (105 µg triphenyl formazan (TPF) g-1 soil 24 hr-1) and increased urease (39 mg NH₄-N g-1 soil hr-1) and phosphatase activities (61 µg PNP g-1 soil hr-1) under field capacity + OM. Herbicide application consistently suppressed microbial and enzymatic activities across all moisture regimes. Recovery of non-target microbial populations beyond control levels suggests that fipronil and its metabolites may serve as nutrient or energy sources for specific soil microorganisms.